BAYESIAN REGRESI SURVIVAL PADA PROSES KEJADIAN HIV/AIDS DI JAWA TIMUR - Nur Mahmudah; Sukono Sukono (LPPM Universitas Terbuka, 2020)
Survival analysis is a statistical procedure that describes a mathematical model that is often applied in various studies, especially in health. One application of survival analysis is to determine the rate of survival and the factors affecting HIV / AIDS sufferers in East Java. HIV / AIDS is a virus that attacks or infects white blood cells, causing a decrease in immune cells. This disease causes a decrease in productivity in the health and economic sectors of a country. Even if the disease continues to increase, the weak economic development will decrease due to the treatment of HIV/AIDS and the risk of death of people infected with the HIV / AIDS virus is getting higher in East Java. In addition to these health and economic quality factors, factors such as residents' knowledge of the disease. By knowing the factors of HIV/AIDS survival rate, mathematical modelling can be done to estimate the duration of the patient's survival power comprehensively and accurately. In this study, we want to find out what factors affect the survival rate of HIV/AIDS using the 3-Parameter Lognormal Survival Link Function model in which the method of parameter estimation used is the Bayesian MCMC-Gibbs Sampling method. The best models is the 3-parameter lognormal survival with frailty that is normally distributed and factors affect the survival rate of HIV/AIDS is education (X3), marital status (X5), Stadium of the patient (X8), adherence of therapy (X10), opportunistic infection (X11) and risk factor of infection (X13). Analisis survival merupakan suatu prosedur statistika yang menjelaskan model matematis yang seringkali diaplikasikan dalam berbagai penelitian, terutama di bidang kesehatan. Salah satu penerapan dari analisis survival adalah untuk mengetahui laju bertahan hidup dan faktor-faktor yang mempengaruhi penderita HIV/AIDS di Jawa Timur. Penyakit HIV/AIDS adalah virus yang menyerang atau menginfeksi sel darah putih yang menyebabkan turunnya sel kekebalan tubuh. Penyakit ini mengakibatkan penurunan produktivitas di bidang kesehatan dan ekonomi di suatu negara. Bahkan apabila penyakit ini terus meningkat maka lemahnya perkembangan ekonomi akan menjadi menurun akibat pengobatan penyakit HIV/AIDS dan resiko kematian dari orang yang terinfeksi virus HIV/AIDS tersebut semakin tinggi di Jawa Timur. Disamping faktor kualitas kesehatan dan ekonomi tersebut, faktor seperti pengetahuan warga terhadap penyakit HIV/AIDS. Dengan mengetahui faktor-faktor laju bertahan hidup penyakit HIV/AIDS dapat dilakukan pemodelan matematis untuk memperkirakan durasi daya survival secara aktual, dan komprehensif. Tujuan artikel dalam penelitian ini adalah menjelaskan faktor-faktor yang mempengaruhi laju bertahan hidup pasien terhadap penyakit HIV/AIDS dengan menggunakan model Survival Lognormal 3 parameter Link Function. Metode estimasi parameter yang digunakan adalah metode Bayesian MCMC-Gibbs Sampling. Model Survival Lognormal 3 Parameter dengan Frailty yang berdistribusi normal menghasilkan faktor-faktor yang mempengaruhi laju bertahan hidup pasien HIV/AIDS di Jawa Timur adalah pendidikan(X3), status perkawinan (X5), stadium penderita (X8), kepatuhan terapi (X10), infeksi oportunitis (X11) dan resiko penularan (X13).